Measuring The Information Content Of Accounting Profits In The Iraqi Banking Sector For Banks Listed On The Iraqi Stock Exchange - Mohammed Farhan Hatem Algayyim; Maytham Bader Bawie Al-Sfan (Harmoni Economics: International Journal of Economics and Accounting, 2024)
The study aims to measure the information content of the accounting profits of banks listed on the Iraqi Stock Exchange, as the sample included 10 banks for a period of 4 years (2016-2019). The study concluded that banks that have a high explanatory ability reflect greater stability in the stock price, which would reassure Investors and stakeholders, thus reducing dispersion and fluctuations in the stock price, while banks with weak explanatory power show higher volatility in the stock price, which indicates additional risks that increase the fluctuation in investor returns, and the influencing factors have a major role in enhancing or reducing the information content of profits. Which explains the discrepancy between banks, and the study recommended the need to enhance the quality of financial disclosure, especially banks with weak explanatory capacity, increase transparency, and work to enhance the informational content of profits, which in turn increases investors’ confidence in accounting information, as well as encouraging banks to strengthen their internal control systems, which helps in Reducing accounting errors and the accuracy of declared profits, thus stabilizing the share price. Strengthening the administrative capabilities of executive managers contributes significantly to enhancing the informational content of profits by allocating the company’s available resources efficiently and effectively.